Fatores associados à hipertensão arterial: o efeito independente do consumo abusivo de álcool - Gisele Marçal Pimenta (2016)
Introduction: Cardiovascular disease (CVD) is the leading cause of death worldwide, accounting for the most significant public health problem today. In this context, hypertension (HT) is highly prevalent and is configured as an independent risk factor for CVD. The World Health Organization (WHO) also highlights the abuse of alcohol as an important public health problem and some studies have identified its association between this lifestyle habits and HT. However, this relationship has not been consistently investigated, particularly in the Brazilian population. Methods: This was an epidemiological, cross-sectional and analytical design, conduct in order to analyze the factors associated with AH with emphasis on the independent effect of alcohol consumption on campus officials health of a public university. A convenience sample consisted of 211 participants, from both genders, aged 20 and 65 years, and data regarding demographic, socioeconomic, anthropometric, dietary, biochemistry, blood pressure, and lifestyle and working conditions were sampled. Hypertension was defined as systolic blood pressure 140 mmHg and or diastolic blood pressure 90 mmHg and or use of antihypertensive medication, while binge drinking was characterized by the consumption of five or more drinks on a single occasion for men and four or more drinks on a single occasion for women. Descriptive (absolute and relative frequencies), bivariate (chi-square test or Fisher's exact Pearson) and multivariate (Poisson regression) statistical analysis, with a 5% significance level, were used. Results: The prevalence of hypertension was 34.1% and binge drinking was observed in 25.1% of participants. The bivariate analysis revealed that binge drinking, men, overweight, abdominal obesity, increased serum concentrations of LDL-C and triglycerides, and time at work > 120 months were associated with HT. After multivariate adjustment, following the proposed theoretical model, binge drinking remained independently associated with hypertension (OR = 1.62, 95% CI 1.16 to 2.28). Conclusion: The prevalence of hypertension and binge drinking were very high and these two important public health problems were strongly related. This finding is relevant, particularly when considering that the study participants were composed predominately of health professionals.